5PSQ-115 'patient experience' for improving patient clinical pathways in an oncology day hospital. (March 2019) - Chatain, C; Durand, M; Curatolo, N; Morellec, S; Barthier, S; Rieutord, A; Decottignies, A
Abstract : Background: Patient engagement is considered critical in improving quality of care provided by the healthcare system. Developed recently by our hospital, the 'Patient experience' is a programme collecting patient's journey experiential feedback with the aim of establishing a continuous improvement method. As part of a project focusing on the improvement of patient's pathways for patients receiving chemotherapy in our oncology day hospital, a 'Patient experience' was carried out. Purpose: The aim was to collect and analyse patients' feedback to improve this care pathway. Material and methods: A map describing the patient's journey was performed to identify the critical steps. An interview guide, focusing on medication management at each step and, more specifically on chemotherapy, was developed and validated with the pharmacists, the oncologist, the head nurse and the nurses. Non-recorded semistructured interviews were conducted by both a student and a pharmacist's resident or alone by a resident until data collection reached saturation point. Patients with communication difficulties, cognitive impairment or severe asthaenia were excluded. The interview's results were summarised in a 'map of emotions'. For each step of the hospital stay, the map presented a positive and negative patient's impression. A general feedback was then delivered to health professionals involved in the project. Results: In total, 20 interviews were conducted. The average age of participants was 62 years (29–82). Among them, 70% (n=14) were treated for less than 6 months. The average interview duration was 21 min (10–45). Overall, the care provided at the hospital received good feedback. The improvement's axes were: the lack of achievement and enrolment for pharmacy interview of patients who had a PICC-line or an oral chemotherapy, for explaining the treatment. Conclusion: These interviews were very informative, highlighting a good overall level of care delivered and allowing us to identify some issues to consider. This innovative method is very customer-focused, leading to the identification of patient's real needs and avoiding top-down solutions sometimes proposed by healthcare professionals, which do not take into account patient's point of view. References and/or acknowledgements: No acknowledgements. No conflict of interest.